Productivity of wheat (Triticum aestivum) and weed competition influenced bydifferent planting techniques and weed competition treatments - GILL, HARMANPREET KAUR; WALIA, UJAGAR SINGH (The Indian Journal of Agricultural Sciences, 2025)
An experiment was conducted during winter (rabi) 2022–23 and 2023–24 at Lovely Professional University, Phagwara, Punjab to study the productivity of wheat (Triticum aestivum L.) and weed competition influenced by different planting techniques and weed competition treatments. The wheat variety used for the experiment was PBW824. The experiment was conducted using a split plot design (SPD) with three replications. The major plots were assigned four different planting patterns, viz. two-rows/bed, three-rows/bed, cross sowing, and flat sowing while in the minor plots, there were four weed competition treatments, viz. competition by Phalaris minor alone; competition by broadleaf weeds (BLW) alone; joint competition (weedy check); and a weed-free treatment (without competition). These treatments were applied to study their effects on crop growth under varying planting patterns and weed competition conditions. Findings revealed that three-rows/bed and cross sowing produced significantly higher grain yield (5039 and 4727 kg/ha) and (5161 and 4662 kg/ha) than two-rows/bed and flat sowing technique. Grain yield also higher in three-rows/bed, bidirectional sowing and two-rows/bed was (11.94 and 10.34%, 14.02 and 9.09% and 4.60 and 4.80%), respectively than flat sowing. In comparison to joint competition there were (24.46 and 29.16%, 9.24 and 14.30% and 17.24 and 23.62%) higher grain yield in weed free treatment, competition by BLW only and competition by Phalaris minor alone. The 35–42 days critical period for crop-weed competition was observed and noticed various weed flora found in wheat field was Phalaris minor, Malva neglecta, Melilotus indica, Medicago sativa, Sonchus arvensis, Argemone mexicana, Lepidium sativum, Veronica spp., Vicia sativa, Anagallis arvensis, Chenopodium album, Fumaria parviflora, Rumex spinosus.